Response of Eggplant (Solanum melongena) Grafted onto Tomato (Solanum lycopersicum) Rootstock to Herbicides. (March 2016) - Chaudhari, Sushila; Jennings, Katherine M.; Monks, David W.; Jordan, David L.; Gunter, Christopher C.; Basinger, Nicholas T.; Louws, Frank J.
Abstract : Tomato rootstocks have been successfully used for eggplant production. However, the safety of herbicides registered in tomato has not been tested on grafted eggplant, which is a combination of tomato rootstock and eggplant scion. Greenhouse and field experiments were conducted to determine response of grafted eggplant on tomato rootstock to napropamide, metribuzin, halosulfuron, trifluralin, S -metolachlor, and fomesafen herbicides. In greenhouse experiments, herbicide treatments included pretransplant S -metolachlor (400 and 800 g ai ha −1 ), pre- or posttransplant metribuzin (140 and 280 g ai ha −1 ), and posttransplant halosulfuron (18 and 36 g ai ha −1 ). In field experiments, herbicide treatments included pretransplant fomesafen (280 and 420 g ai ha −1 ), halosulfuron (39 and 52 g ha −1 ), metribuzin (280 and 550 g ha −1 ), napropamide (1, 120 and 2, 240 g ai ha −1 ), S -metolachlor (800 and 1, 060 g ha −1 ), and trifluralin (560 and 840 g ai ha −1 ). The eggplant cultivar 'Santana' was used as the scion and nongrafted control, and two hybrid tomatoes 'RST-04−106-T' and 'Maxifort' were used as rootstocks for grafted plants. In both greenhouse and field experiments, there was no difference between grafted and nongrafted eggplant in terms of injury caused by herbicides. Metribuzin posttransplant at 140 and 280 g ha −1 caused 94 and 100% injury to grafted and nongrafted eggplant 4 wk after treatment. In field experiments, pretransplant fomesafen, napropamide, S -metolachlor, and trifluralin caused less than 10% injury and no yield reduction in grafted and nongrafted eggplant. However, metribuzin caused injury and yield reduction in both grafted and nongrafted eggplant. Metribuzin at 550 g ha −1 caused 60 and 81% plant stand loss in 2013 and 2014, respectively. Halosulfuron reduced yield 24% in both grafted and nongrafted eggplant compared to nontreated control in 2013 but did not reduce yield in 2014. The pretransplant S -metolachlor, napropamide, fomesafen, and trifluralin are safe to use on eggplant grafted onto tomato rootstock, and will be a valuable addition to the toolkit of eggplant growers.